2015
DOI: 10.17762/ijritcc2321-8169.1504114
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Energy Efficient Routing In MANETs Using MultiObjective Genetic Algorithm

Abstract: Abstract-Mobile ad hoc networks (MANET) are self-establishing network that contains short radio range and limited bandwidth and they do not have any specified infrastructure. The ad hoc network changes its topology suddenly. In such this type of situation, establishing correct and efficient routes from source to destination is an important design issue in mobile ad hoc networks and its challenging goal is to provide energy efficient routing protocol. For finding the shortest path between the sources to destina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…An innovative method using a genetic algorithm for energy-efficient routing in mobile ad hoc networks has been reported by Neha Agarwal and Neeraj Manglani [38]. When one path fails, this algorithm offers the best option for transmitting data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An innovative method using a genetic algorithm for energy-efficient routing in mobile ad hoc networks has been reported by Neha Agarwal and Neeraj Manglani [38]. When one path fails, this algorithm offers the best option for transmitting data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The SIm AODV [10] has the capable to prevent packet loss owed by Black Hole Attack, Cosmic Dust Attack, Link Break, and Node Intrusion by the malicious and un believable nodes. But SIm AODV has two major problems one is it does not has the mechanism to prevent active attacks [5]. Second one is end-to-end delay is more compare to the normal AODV.…”
Section: Contributionmentioning
confidence: 99%
“…The rc is calculated based on the link quality and the traffic demand. Neha Agarwal [5] et al In this paper, a new energy efficient routing protocol in MANETs using genetic algorithm has been proposed. In the literature it has been found that Genetic algorithms can be used in routing protocols for mobile ad hoc networks.…”
Section: Contributionmentioning
confidence: 99%
See 1 more Smart Citation